2021
DOI: 10.1002/brb3.2231
|View full text |Cite
|
Sign up to set email alerts
|

The GLP‐1/GIP dual‐receptor agonist DA5‐CH inhibits the NF‐κB inflammatory pathway in the MPTP mouse model of Parkinson's disease more effectively than the GLP‐1 single‐receptor agonist NLY01

Abstract: The GLP-1 receptor agonist exendin-4 has recently shown good effects in a phase II clinical trial in Parkinson's disease (PD) patients. Here, a comparison of the new GLP-1/GIP dual receptor agonist DA5-CH and NLY01, a 40 kDa pegylated form of exendin-4, on motor impairments and reducing inflammation in the 1-methyl-4-phenyl-1,2,3,6tetrahydropyridine (MPTP) PD mouse model is provided. The drug groups received either DA5-CH or NLY01 (25 nmol/kg) i.p. after daily MPTP intraperitoneal injection.Both drugs showed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 85 publications
(115 reference statements)
2
43
0
Order By: Relevance
“…Crucially, all forementioned GLP-1 analogs and GLP-1R/GIPR dual agonists cross the BBB in vivo , albeit at varying rates. In comparison, DA4-JC4 (t 1/2 = 151.94 min) and, similarly, DA5-CH showed the highest BBB penetration rates, followed by medium BBB translocation of Exendin-4, lixisenatide and DA3-CH as well as poor brain influx of the lipidated peptides liraglutide, semaglutide, DA1-JC as well as the PEGylated DA2 and NLY01, a variant of Exendin-4 with prolonged t 1/2 ( Li et al, 2020a ; Salameh et al, 2020 ; Zhang et al, 2020 ; Lv et al, 2021 ). We confirmed that GLP-1R/GIPR dual agonists demonstrated superior neuroprotective effects compared to other synthetic GLP-1 analogs in AD ( Maskery et al, 2020 ; Salles et al, 2020 ) and PD ( Yuan et al, 2017 ; Feng et al, 2018 ; Zhang and Holscher, 2020 ; Lv et al, 2021 ; Zhang L.Y.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Crucially, all forementioned GLP-1 analogs and GLP-1R/GIPR dual agonists cross the BBB in vivo , albeit at varying rates. In comparison, DA4-JC4 (t 1/2 = 151.94 min) and, similarly, DA5-CH showed the highest BBB penetration rates, followed by medium BBB translocation of Exendin-4, lixisenatide and DA3-CH as well as poor brain influx of the lipidated peptides liraglutide, semaglutide, DA1-JC as well as the PEGylated DA2 and NLY01, a variant of Exendin-4 with prolonged t 1/2 ( Li et al, 2020a ; Salameh et al, 2020 ; Zhang et al, 2020 ; Lv et al, 2021 ). We confirmed that GLP-1R/GIPR dual agonists demonstrated superior neuroprotective effects compared to other synthetic GLP-1 analogs in AD ( Maskery et al, 2020 ; Salles et al, 2020 ) and PD ( Yuan et al, 2017 ; Feng et al, 2018 ; Zhang and Holscher, 2020 ; Lv et al, 2021 ; Zhang L.Y.…”
Section: Introductionmentioning
confidence: 93%
“…Various studies confirm that GLP-1 analogs show potent anti-inflammatory effects. Liraglutide, lixisenatide, semaglutide, exendin-4 or NLY01 [a pegylated and rather poorly BBB-penetrant version of Exendin-4 ( Yun et al, 2018 ; Lv et al, 2021 ; Park et al, 2021 )] reduced IBA-1 or Mac-1 immunoreactivity, indicative of microgliosis, in the hippocampus ( Cai et al, 2018 ; Holubova et al, 2019 ; Salles et al, 2020 ; Paladugu et al, 2021 ; Park et al, 2021 ), cortex ( McClean et al, 2011 , 2015 ; Long-Smith et al, 2013 ; Paladugu et al, 2021 ) and global brain tissue ( McClean and Holscher, 2014a ) of aged WT, APP/PS1, 5xFAD, 3 × Tg-AD or sporadic STZ AD mice. Likewise, microgliosis was attenuated by GLP-1R agonists the SN pars compacta (SNpc) ( Kim et al, 2009 ; Feng et al, 2018 ; Zhang et al, 2018 , 2019 , 2020 ), striatum ( Kim et al, 2009 ; Yun et al, 2018 ) or cortex ( Yuan et al, 2017 ) of MPTP or α-synuclein-injected mice.…”
Section: Inflammationmentioning
confidence: 99%
“…Numerous studies focusing on diverse brain illnesses such as Alzheimer's disease (AD) and ischemic brain injury have corroborated the localization of GLP-1R in the CNS. [32][33][34] In addition, a study reported GLP-1R expression on pericytes, which are multi-functional mural cells located at the center of the neurovascular unit (NVU). 35 Other studies have mapped the action of GLP-1RAs, demonstrating that GABA neurons in the NTS express GLP-1 receptors and mediate the anorectic effects of liraglutide in rats.…”
Section: The Physiology Of the Interactions Between Glp-1ras And The ...mentioning
confidence: 99%
“…46 Several preclinical and clinical studies on ischemia-induced brain injury, Alzheimer's disease (AD), Parkinson's disease (PD), and other neurodegenerative disorders have established that GLP-1RAs can cross the BBB and exert a significant neuroprotective effect. [32][33][34] Furthermore, various studies have examined the anorexia-promoting properties of GLP-1RAs. The studies have demonstrated that GLP-1R is also expressed in nuclei controlling food intake, such as the arcuate nucleus (ARC) and paraventricular thalamic nucleus (PVN).…”
Section: Native Glp-1 Glp-1ras and Bbbmentioning
confidence: 99%
“…Mice received 20 mg/kg/day MPTP in saline i.p. for seven consecutive days, a dose that previously showed good effects (Li et al, 2016;Lv et al, 2021). Simultaneously, starting on the first day of MPTP injections, the CCK analogue and liraglutide were administered for 14 consecutive days injection once-daily.…”
Section: Animalsmentioning
confidence: 99%